Secretin Regulates Excitatory GABAergic Neurotransmission to GnRH Neurons via Retrograde NO Signaling Pathway in Mice - Veronika Csillag; Veronika Csillag; Csaba Vastagh; Zsolt Liposits; Zsolt Liposits; Imre Farkas (Frontiers in Cellular Neuroscience, 2019)
In mammals, reproduction is regulated by a wide range of metabolic hormones that maintain the proper energy balance. In addition to regulating feeding and energy expenditure, these metabolic messengers also modulate the functional performance of the hypothalamic-pituitary-gonadal (HPG) axis. Secretin, a member of the secretin-glucagon-vasoactive intestinal peptide hormone family, has been shown to alter reproduction centrally, although the underlying mechanisms have not been explored yet. In order to elucidate its central action in the neuroendocrine regulation of reproduction, in vitro electrophysiological slice experiments were carried out on GnRH-GFP neurons in male mice. Bath application of secretin (100 nM) significantly increased the frequency of the spontaneous postsynaptic currents (sPSCs) to 118.0 ± 2.64% compared to the control, and that of the GABAergic miniature postsynaptic currents (mPSCs) to 147.6 ± 19.19%. Resting membrane potential became depolarized by 12.74 ± 4.539 mV after secretin treatment. Frequency of evoked action potentials (APs) also increased to 144.3 ± 10.8%. The secretin-triggered elevation of the frequency of mPSCs was prevented by using either a secretin receptor antagonist (3 μM) or intracellularly applied G-protein-coupled receptor blocker (GDP-β-S; 2 mM) supporting the involvement of secretin receptor in the process. Regarding the actions downstream to secretin receptor, intracellular blockade of protein kinase A (PKA) with KT-5720 (2 μM) or intracellular inhibition of the neuronal nitric oxide synthase (nNOS) by NPLA (1 μM) abolished the stimulatory effect of secretin on mPSCs. These data suggest that secretin acts on GnRH neurons via secretin receptors whose activation triggers the cAMP/PKA/nNOS signaling pathway resulting in nitric oxide release and in the presynaptic terminals this retrograde NO machinery regulates the GABAergic input to GnRH neurons.